Fructose-rich diet leads to reduced aerobic capacity and to liver injury in rats - Botezelli, Jose Diego [UNESP]; Cambri, Lucieli Teresa [UNESP]; Ghezzi, Ana Carolina [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Voltarelli, Fabricio Azevedo; Rostom de Mello, Maria Alice [UNESP] (Biomed Central Ltd., 2012)
The main purpose of this research was to investigate the alterations in the aerobic capacity and appearance of metabolic alterations in Wistar rats fed on fructose-rich diet. We separated twenty-eight rats into two groups according to diet: a control group (C) (balanced diet) and a fructose-rich diet group (F). The animals were fed these diets for 60 d (d 120 to 180). We performed insulin, glucose as well as a minimum lactate test, at d 120 and 180. At the end of the experiment, sixteen animals were euthanized, and the following main variables were analysed: aerobic capacity, the serum aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio, serum and liver triglyceride concentrations, serum and liver thiobarbituric acid reactive substance (TBARS) concentrations, serum and liver catalase and superoxide dismutase (SOD) activity and haematoxylin-eosin histology (HE) in hepatocytes. The remaining twelve animals were submitted to an analysis of their hepatic lipogenic rate. The animals fed a fructose-rich diet exhibited a reduction in aerobic capacity, glucose tolerance and insulin sensitivity and increased concentrations of triglycerides and TBARS in the liver. Catalase and SOD activities were reduced in the livers of the fructose-fed animals. In addition, the serum AST/ALT ratio was higher than that of the C group, which indicates hepatic damage, and the damage was confirmed by histology. In conclusion, the fructose-rich diet caused significant liver damage and a reduction in insulin sensitivity in the animals, which could lead to deleterious metabolic effects.
Keywords: Fructose; Liver injury; Oxidative stress; Rats